The Effect of Using Flipbook Media on Imaginative Description Paragraph Writing Skills in Elementary School Students - Mitha, Elvin Dea; Basri, Amin (research, training and philanthropy institution Natural Aceh, 2024)
Generally, the problem in the learning process is the application of the lecture method in the delivery of learning material by the teacher. The teacher also leads students to complete assignments, discussions, exercises, and question-and-answer activities like general learning methods. An alternative way of looking at students' writing skills is by using flipbook media. This research aims to determine the influence of flipbook media on imaginative descriptive paragraph writing skills at Pertiwi Elementary School, Medan. The type of research used is quasi-experimental with a nonequivalent control group design research design. The samples used were class IV A students at Pertiwi Medan Elementary School as the control class and class IV B students at Pertiwi Medan Elementary School as the control class, with 24 students in each class. Data collection techniques use test and observation techniques. Meanwhile, data analysis techniques use instrument and data analysis tests using research results using IBM SPSS for Windows 20 and Excel. Based on the research results, the flipbook media significantly influences the imaginative descriptive paragraph writing skills of Pertiwi Elementary School students in Medan, and the results of the comparison of the average pre-test score were 51.88 and post-test 85.83.